Use of social media for livestock advisory services: The case of WhatsApp in Himachal Pradesh, India - THAKUR, DEVESH; CHANDER, MAHESH (The Indian Journal of Animal Sciences, 2017)
The opportunities of information access to livestock owners especially from institutional sources are minimal under Indian context. Social media tools such as WhatsApp have remarkable ability to reduce the transaction cost as well as increase the coverage of extension services. WhatsApp, a hugely popular medium of information exchange can be a cost-effective tool to improve livestock advisory services since skilful use of WhatsApp can overcome limitations of time and geographical barriers faced by these services. The current study explored and experimented with the possibility of using WhatsApp in livestock advisory work. Under the experimental study, WhatsApp emerged as a most preferred choice of referring to a diverse set of livestock-related information. Furthermore, advice through WhatsApp helped farmers in seeking the timely interventions and information support from other relevant sources. Hence, state development departments must promote its use through suitable models among which one discussed in this paper to enhance the scope and coverage of livestock advisory services.